Complete mitochondrial genome of Oregonia gracilis Dana, 1851 (Crustacea: Decapoda: Majoidea) - Lee, Sang-Hui (Mitochondrial DNA B Resour, 2021)
The complete mitochondrial genome of the majoid crab, Oregonia gracilis, was determined from a specimen collected in Korea. The mitochondrial genome is 15,737 bp long and contains 13 protein-coding genes (PCGs), 22 transfer RNA (tRNA) genes, and two ribosomal RNA (rRNA) genes. A maximum-likelihood phylogenetic tree based on the 13 PCGs of the mitochondria showed that O. gracilis is closely related to the genus Chinoecetes. The complete mitochondrial genome of O. gracilis provides valuable information on the mitochondrial evolution of majoid crabs.